RECREATIONAL ACTIVITY OF WOMEN AGED 50+ IN THE LARGE CITY ENVIRONMENT - Marzec, Arkadiusz; Pekarcik, Lubomir; Wożniak, Waldemar (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The number of older adults is increasing in all European countries and these tendencies are also noticeable in Poland. Maintaining a good psychophysical status through participation in various forms of activity is known to be the precondition for successful ageing. The family status of older adults is characterized by feminization (the major part of the population of older adults is women). Older adults in Poland report their health status as poor and feel lonely. To address this problem, the Long-Term Senior Policy for 2014-2020 specified the areas of corrective measures where recreational activity takes top place. The best form of physical activity for seniors is physical recreation which is connected with relax while performing stimulating, adaptive, compensating, informational or hedonist functions. Many cities in Poland are engaged in the initiatives aimed at older women and implement extended local programs of activation for older adults. The study presents the forms of support for activity in the urban environment of Częstochowa, with particular focus on recreational activity of women aged 50+.